A strategic discovery roadmap towards high-quality leads and drug development candidates for kinetoplastid diseases. Part 3: from lead towards a drug development candidate - Hendrickx, Sarah; Ilbeigi, Kayhan; Thore, Eli S. J.; Bertram, Michael G.; Calvo-Alvarez, Estefania; Cintesun, Sener; Olias-Molero, Ana Isabel; Corral, Maria Jesus; Mateo-Barrientos, Marta; Estaquier, Jerome; Pomel, Sebastien; Alunda, Jose Maria; et al. (OXFORD UNIV PRESS, 2026)
Neglected tropical diseases such as leishmaniasis, Chagas disease, sleeping sickness and animal trypanosomiasis remain a significant global health challenge. This part of the roadmap outlines a streamlined path for progressing from lead identification to a drug development candidate, tailored to the specific needs of kinetoplastid infections. Besides the medicinal upscaling of synthesis, this review highlights key experiments in pharmacology in non-rodent species, toxicology, pharmacokinetics and pharmaceutics. These include but are not limited to early evaluation of safety using refined in vitro and in vivo methods to enhance predictive value, bioavailability and distribution to target tissues, and formulation strategies leveraging various delivery systems to optimize efficacy and safety. Environmental toxicity is also addressed proactively, for which in silico tools are presented. Collectively, this roadmap provides a practical, scalable approach to deliver high-quality drug candidates capable of addressing the urgent needs for kinetoplastid diseases (Figure 1).
Keywords: LEISHMANIA-INFANTUM; IN-VITRO; CANINE LEISHMANIASIS; EXPERIMENTAL-MODEL; VISCERAL LEISHMANIASIS; CHRONIC CARDIOMYOPATHY; RHESUS MACAQUES; MACACA-MULATTA; CHAGAS-DISEASE; ANIMAL-MODELS; Infectious Diseases; Microbiology; Pharmacology & Pharmacy